Treatment with Platelet-Rich Plasma: an Evidence Based Case Report of Leprosy Ulcers - Muslimin, Muslimin; Banundari, Rachmawati; Kabulrachman, Kabulrachman (RSUP Dr. Kariadi, 2026)
Introduction: Leprosy foot ulcers occur in patients with leprosy-related neurological disorders and are classified as grade 2 disabilities. These chronic, non-healing ulcers represent a significant clinical challenge. Platelet rich plasma (PRP) application has emerged as a breakthrough treatment. Case report: Two females (aged 48 and 58) with multibacillary leprosy presented with chronic midfoot ulcers persisting for 16 and 24 weeks. At baseline, ulcer areas were measured and biopsies were performed to assess TGF-β1, PDGF, and collagen density. Follow-up measurements for biomarkers occurred on day 13, and ulcer area was reassessed on day 41. Discussion: Both patients received standard therapy plus PRP, resulting in reduced ulcer area, increased TGF-β1, and higher collagen density. PDGF levels increased in one patient but decreased in the other. PRP promotes epithelial and endothelial cell proliferation during neovascularization and stimulates extracellular matrix synthesis. Furthermore, it modulates the inflammatory response, facilitating tissue regeneration by balancing the immune system. Conclusion: Combining standard therapy with PRP shows strong potential for healing chronic leprosy ulcers. Results demonstrated reduced ulcer area, increased TGF-β1, and improved collagen density, though PDGF levels remained inconsistent